Evaluation and optimization of flocculation-sedimentation-filtration process for addressing water-energy nexus challenges at Kemper IGCC power plant: Bench and pilot scale studies - Abhijit Bhagavatula (Elsevier, 2021)
The coal processing system at the Kemper County IGCC power plant featured a fluidized bed dryer system to dry high moisture lignite (> 45%). The system evaporated a large amount of water (60–70 KPPH) that was then used in other plant processes. The evaporated water contained 0.1–0.3% ultrafine particles (d50 of < 3 μm), which caused problems for the filtration system. A novel flocculation-sedimentation with membrane (FSM) filtration process was developed to filter ultrafine particles from the slurry water so it could be used in downstream gasification processes. Bench and pilot scale studies were designed to optimize process parameters such as polymer dilution, flocculant dosage and settling times. Using the optimum polymer dosage obtained from bench scale studies, several pilot scale tests were performed using a slipstream of the process slurry from the ''First-of-its-kind'' Kemper IGCC power plant. The FSM process achieved more than 99% removal of ultrafine suspended solids with a 10-fold increase in the filtration flux rates when compared to standard (ePTFE) membrane filtration. Furthermore, a cleaning process was successfully devised for regenerating the filter media if they were plugged due to operational upsets. The filter media can be cleaned and effectively regenerated by soaking them in 2% bleach solution for 1.5 h. The flux rates obtained after filter media regeneration were comparable to the flux rates obtained on new filter media.